Butterfly tree - Markle, Sandra; Wu, Leslie (Atlanta, Ga. : Peachtree, 2011)
When Jilly encounters a mysterious orange cloud on a family outing to Lake Erie, she and her mother go to investigate the phenomenon. Includes facts about monarch butterflies.
Keywords: Monarch butterfly -- Migration; Butterflies; Monarch butterfly -- Migration; Butterflies; Monarch butterflies -- Migration; Butterflies